Adjuvant and neoadjuvant breast cancer treatments: A systematic review of their effects on mortality. (April 2022) - Kerr, Amanda J.; Dodwell, David; McGale, Paul; Holt, Francesca; Duane, Fran; Mannu, Gurdeep; Darby, Sarah C.; Taylor, Carolyn W.
Highlights: Clinical guidelines recommend > 20 adjuvant or neoadjuvant breast cancer options. Randomised data on 1000–10, 000 women are available for most options. Breast cancer mortality or recurrence was reduced by 10–25% for most options. Anthracycline chemotherapy and radiotherapy increased non-breast-cancer mortality. Radiotherapy-related risks increased with increasing organ dose. Abstract: Background: Adjuvant and neoadjuvant breast cancer treatments can reduce breast cancer mortality but may increase mortality from other causes. Information regarding treatment benefits and risks is scattered widely through the literature. To inform clinical practice we collated and reviewed the highest quality evidence. Methods: Guidelines were searched to identify adjuvant or neoadjuvant treatment options recommended in early invasive breast cancer. For each option, systematic literature searches identified the highest-ranking evidence. For radiotherapy risks, searches for dose–response relationships and modern organ doses were also undertaken. Results: Treatment options recommended in the USA and elsewhere included chemotherapy (anthracycline, taxane, platinum, capecitabine), anti-human epidermal growth factor 2 therapy (trastuzumab, pertuzumab, trastuzumab emtansine, neratinib), endocrine therapy (tamoxifen, aromatase inhibitor, ovarian ablation/suppression) and bisphosphonates. Radiotherapy options were after breast conserving surgery (whole breast, partial breast, tumour bed boost, regional nodes) and after mastectomy (chest wall, regional nodes). Treatment options were supported by randomised evidence, including > 10, 000 women for eight treatment comparisons, 1, 000–10, 000 for fifteen and < 1, 000 for one. Most treatment comparisons reduced breast cancer mortality or recurrence by 10–25%, with no increase in non-breast-cancer death. Anthracycline chemotherapy and radiotherapy increased overall non-breast-cancer mortality. Anthracycline risk was from heart disease and leukaemia. Radiation-risks were mainly from heart disease, lung cancer and oesophageal cancer, and increased with increasing heart, lung and oesophagus radiation doses respectively. Taxanes increased leukaemia risk. Conclusions: These benefits and risks inform treatment decisions for individuals and recommendations for groups of women.